2010
DOI: 10.3390/medicina46050045
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of metastatic tumors of the femur

Abstract: Objective. To evaluate the patients functional outcome and pain control after resection of metastatic femoral tumors. Material and methods. A prospective randomized clinical study was conducted, which included 26 cases of metastatic tumors of the femur with an associated pathologic fracture. These selected cases were randomly divided into two groups based upon the using of methylmethacrylate cement in fracture fixation. Group 1 (n=13) included all cases where the fractures were treated with bone cement augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…studies that also include primary tumors, other anatomical areas, or revision procedures without reporting results separately). We contacted authors if studies published after the year 2000 included indiscernible treatment arms but were otherwise eligible (20 studies) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Only one of these could eventually be included [8].…”
Section: Article Selectionmentioning
confidence: 99%
“…studies that also include primary tumors, other anatomical areas, or revision procedures without reporting results separately). We contacted authors if studies published after the year 2000 included indiscernible treatment arms but were otherwise eligible (20 studies) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Only one of these could eventually be included [8].…”
Section: Article Selectionmentioning
confidence: 99%
“…The exact histological diagnosis is of clinical significance to the surgical management of pathological fractures by informing accurate prognosis. 21 24 The representation of histotypes with intent-to-cure options in both patients with (>30%) and without (60%) malignant history was higher than expected. Zhang et.…”
Section: Discussionmentioning
confidence: 81%
“…Local treatment includes surgery and radiation therapy, with the aim of relieving pain and improving QOL. 15–17 The indications for surgery are prognosis, ability to tolerate surgery, and possible functional recovery, fixation, and support of fractured parts. 18 However, in the terminal stage of cancer, aggressive treatment is generally difficult, and it has been reported that systemic and local complications after surgery also occur at a high rate.…”
Section: Discussionmentioning
confidence: 99%